Bimbingan dan Latihan melalui Program In House Training untuk Meningkatkan Profesionalisme Guru - Safrida Safrida (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2022)
Limitations of the teacher's ability to innovate in classroom learning result in low learning outcomes for learners. So that this becomes a special note on supervision activities that are routinely carried out by the principal. the purpose of this research is to provide guidance and exercises to teachers in implementing the learning models suggested in K-13 to be used in the classroom. The research method used is school action research, with the number of study subjects as many as 29 teachers. Instrume used in the form of worksheets and observation sheets. Analysis of the data used uses deceptive statistics. The results showed that there was an increase in the competence of teacher professionalism in applying the learning model in the classroom through the in-house training program. Therefore, this IHT program is highly recommended to be used in various training to help teachers who are struggling and want to develop themselves